A review of Antillocladius Sæther and Litocladius Mendes, Andersen et Sæther, with the description of two new Neotropical genera (Diptera, Chironomidae, Orthocladiinae) - Mendes, Humberto Fonseca; Andersen, Trond (Zootaxa, 2008)
The genus Antillocladius Sæther, 1981 currently comprises 17 described species. In the present paper, seven new Brazilian species, A. atalaia sp. n., A. axitiosus sp. n., A. brazuca sp. n., A. campususp sp. n., A. gephyrus sp. n., A. plicatus sp. n., and A. ultimus sp. n. are described and illustrated as males, and Parametriocnemus subnubilus Sinharay et Chaudhuri, 1979 from India is transferred to Antillocladius. Two new species of the closely related genus, Litocladius Mendes, Andersen et Sæther, 2004, L. floripa sp. n. and L. confusus sp. n., are described and figured as males. Two new Neotropical genera are described and figured. Gravatamberus gen. n. with five included species, G. apicalus sp. n., G. curtus sp. n., G. guatemaltecus sp. n., G. nidularium sp. n., and G. pilosus sp. n., is based on larva, pupa, and male. Lyrocladius gen. n. with the single included species L. radulatus sp. n. is based on the male only. Keys to orthoclad genera with scalpellate acrostichals and to the males of the included genera are provided. According to the cladogram presented, three monophyletic groups can be recognized; one composed of Antillocladius, Litocladius and Lyrocladius; one composed of Compterosmittia Sæther, Hanocladius Wang et Sæther, Limnophyes Eaton and Paralimnophyes Brundin; and a third, composed of Gravatamberus, Genus H sensu Epler, and Gynocladius Mendes, Sæther et Andrade-Morraye.